Challenges in prenatal diagnosis of beta thalassaemia: couples with normal HbA2 in one partner. (11th November 2015) - Gorivale, Manju; Sawant, Pratibha; Mehta, Pallavi; Nadkarni, Anita; Ghosh, Kanjaksha; Colah, Roshan
Abstract: Objectives: To undertake β ‐genotyping in couples having normal/borderline HbA2 levels in one partner to offer the possibility of prenatal diagnosis of thalassaemia. Methods: A total of 967 couples were screened for β ‐thalassaemia. Haematological analysis was carried out on a Sysmex K‐1000 analyser. The HbA2 and HbF levels were measured by High Performance Liquid Chromatography‐Variant II analyser (Bio‐Rad, USA). β ‐globin gene analysis was done by reverse dot blot hybridization, amplification refractory mutation system or DNA sequencing. Alpha globin gene triplication was determined by Multiplex PCR. Results: In 33 of 967 couples, one partner had a normal/borderline HbA2 level (1–3.5%); however a β ‐thalassaemia mutation could be identified in 24 of these individuals. Molecular analysis of the β ‐globin gene revealed the presence of the capsite +1 (A → C) [HBB: c.‐50 A → C] mutation in 15 cases (60%), Poly A(T → C) [HBB: c.*110 T → C] mutation in two cases (8%), IVS 1‐5 (G → C) [HBB: c. 92 + 5 (G → C)] mutation in four cases (17%) and the CD 15 (G → A) [HBB: c. 47 G → A] mutation, CD 16 (−C) [HBB: c. 51 del C] mutation and CD 30 (G → C) [HBB: c. 93 G → C] mutation in one case each (4%). Alpha gene triplication was found in five cases, while four cases remained uncharacterized. Conclusions: β ‐genotyping should always be done in a couple if one partner is a β ‐thalassaemia carrier irrespective of the RBC indices and HbA2 levels of the other partner. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Prenatal diagnosis is the most effective approach to reduce the burden of β‐thalassaemia. An increased HbA2 level is the hallmark of diagnosis of β ‐thalassaemia carriers. However, sometimes a couple at‐risk may go unidentified if one partner has normal/borderline HbA2 levels, particularly if they do not have an earlier affected child. What does this study add? This poses a diagnostic challenge, and molecular analysis becomes critical for identifying such couples.